2006
DOI: 10.1016/j.pcrj.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Measures to improve knowledge and self-care among patients with COPD: a UK general practice audit

Abstract: SummaryThe Parchmore Partnership, London, audited 11 evidence-based criteria relating to patient knowledge and COPD morbidity during December 2004 to March 2005 using questionnaires and practice records. 32 patients with moderate to severe COPD participated, and during the project they received information and extra care. Patient knowledge and clinical indicators showed significant improvements. Crown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Ranking thirdly were telephone services, which are emerging as a special form of nurse clinics (Wong et al. 2005, Fernandes et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ranking thirdly were telephone services, which are emerging as a special form of nurse clinics (Wong et al. 2005, Fernandes et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
“…(2005) provided a structured, individualised, educational and supportive dyspnoea management telephone programme after discharge from hospital. Fernandes et al. (2006) studied the effects of telephone calls when weather forecast was worsening, combined with provision of an information pack and a fast‐track treatment in the healthcare system when patients contacted the system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2006, it was estimated that 92.7% of high-risk smokers in the UK received advice, or support to quit (96). The outcomes of audits showed that the percentage of patients with COPD offered smoking cessation advice rose from 81% in December 2004 to 96% by March 2005 (97), indicating that the QOF system is succeeding in encouraging GPs to meet healthcare targets. However, there are one or two criticisms of the scheme.…”
Section: Implementation Of Multimodal Approach and Influential Stratementioning
confidence: 99%